Challenges in embracing virtual reality from healthcare professional’s perspective: a qualitative study - Ismail Mohd Saiboon; Mohd Hisham Mohd Isa; Alias Mahmud; Zaleha Abdullah Mahdy; Nazimi Abd Jabar; Ixora Kamisan@Atan; Mohammad Nazir Ahmad@Sharif; Mohd Ismawira Mohd Ismail (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Virtual reality (VR) in healthcare is relatively new concept and the views of healthcare professionals (HCPs) on its potential should be studied. We set out to investigate the perception of HCPs concerning VR’s feasibility and utility in healthcare. An exploratory qualitative study was conducted among HCPs in a medical teaching institution in the Klang Valley, Malaysia from March until July 2021. Focus group discussions were held using semi-structured questions consisting of four categories i.e., utility, training, development and resources and obstacles were developed deductively prior to the study. They were analysed using thematic coding. The data were presented in the form of categories, themes and quotes. Seven doctors, four allied health professionals and four science officers were among the fifteen respondents. A total of 16 themes were derived out of the four categories which were usage, purpose, new modality, individual experience, patient safety, trainer trainer safety, training standardisation, logistic, interactivity, cost to consumers, potentiality, management support, limitation, funding, lack of expertise, and mindset ignorance. Apart from safety concerns, high VR technology costs were expected to become more affordable in the future. Cybersickness was also of a concern. This study demonstrated that VR was feasible in healthcare education and practice if several critical factors were considered, including increased funding, a more favourable mindset, increased visibility, awareness of available resources and increased collaboration between technical and subject matter experts. As VR acts as simulation, VR ensures trainee's, teacher's and patient's safety while allowing more flexible training in a variety of clinical scenarios.